1996
DOI: 10.1007/bf02318965
|View full text |Cite
|
Sign up to set email alerts
|

The initiation of callus and regeneration from callus culture ofTulipa gesneriana

Abstract: Cold treatment of seeds, obtained from crosses between cultivars of T. gesneriana L., affects the developmental stage of embryos, which in turn influences the frequency of callus induction and the development of different callus types. Cold-treated, mature embryos and basal segments of in vitro-derived bulblets, were suitable explants for the initiation of regenerative callus on medium with 2,4-dichlorophenoxyacetic acid. The bulblets were initiated on flower-stalk segments from cold-stored bulbs of T. gesneri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…However, at the lowest concentration of 2,4-D (1 μM), adventitious roots developed. Famelaer et al (1996) obtained similar results in in vitro tulip culture. Root formation was observed on Tulipa "Christmas Marvel" calluses cultured on medium with 2,4-D, but not on medium with Picloram.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, at the lowest concentration of 2,4-D (1 μM), adventitious roots developed. Famelaer et al (1996) obtained similar results in in vitro tulip culture. Root formation was observed on Tulipa "Christmas Marvel" calluses cultured on medium with 2,4-D, but not on medium with Picloram.…”
Section: Resultssupporting
confidence: 89%
“…al. 1992;Kuijpers and Langens-Gerrits, 1997;Le Nard and Chanteloube, 1992;Podwyszyńska, 2003) or immature embryos isolated from mature seeds (Famelaer, 1996) has been reported, but the propagation factor and the growth rate were still low. The most convenient way of regeneration is through somatic embryogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…According to De Hertogh and Le Nard ( 1993 ), germination begins within a few days of seed hydration, as also confirmed with T. kaufmanniana (Rouhi et al 2010 ). Cold-treated seeds of Tulipa gesneriana germinated after 5–6 wk (Famelaer et al 1996 ). In this study, germination was not observed until 6 mo, as in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The morphogenic response of the explants depends on the presence and concentration of growth regulators in the medium (Gaspar et al 2003 ). To initiate organogenesis in tulips, BAP is usually used, either alone or with auxin (Wright and Alderson 1980 ; Taeb and Alderson 1990 ; Minas 2007 ), although Famelaer et al ( 1996 ) used only picloram and 2,4-dichlorophenoxyacetic acid (2,4-D) to obtain callus tissue. In this study, only 0.5 μM BAP was used to stimulate organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(Krikorian and Kann, 1981), Lilium spp. (Priyadarshi and Sen, 1992;Wickremesinhe et al, 1994;Godo et al, 1998;Nakano et al, 2000) and Tulipa gesneriana (Famelaer et al, 1996). Somatic embryogenesis protocols have also been developed for several species of native Australian rushes (Panaia et al, 2004a,b).…”
Section: Introductionmentioning
confidence: 98%